Levels of growth factors in the lungs affected by cancer with preventive effect of 1,3-diethylbenzimidazolium triiodide in the experiment - E. M. Frantsiyants; I. V. Kaplieva; L. K. Trepitaki (Исследования и практика в медицине)
Purpose of the study. Analyzing the dynamics of VEGF-А, TGF-β and their receptors in the lung tissues in rats with antitumor effect of 1,3-diethylbenzimidazolium triiodide (Stellanin).Material and methods. The study included white outbred rats weighing 180–220 g. The main group included males (n=27) and females (n=27) with sarcoma 45 (s45) inoculated into the subclavian vein but not developed in the lungs (2×106 cells in 0.5 ml of saline) due to the subsequent intragastric administration of Stellanin (0.4 mg/kg once a day) according to an intermittent scheme: administration for 5 days and a break for 2 days. The control group included males (n=14) and females (n=14) without treatment with growing s45 in the lungs. Intact groups included 5 males and 5 females. After 4, 5 and 8 weeks of the experiment animals were decapitated, and levels of VEGF-A, sVEGF-R1, sVEGF-R2, TGF-β and sTGFβR2 were measured in 10% lung homogenates by ELISA (CUSABIO BIOTECH Co., Ltd., China).Results. Lung tissues of intact females showed 1.4 times (p<0.05) lower VEGF-А and 3.3 times higher sVEGF-R1, compared to males. The development of tumors in all control rats was accompanied by the VEGF-А increase (by 1.6–3.0 times) and the TGF-β reduction (by 3 times). The dynamics of both VEGF receptors differed in males and females. The levels of sVEGF-R1 in males increased by 1.5 times (p<0.05), while in females it decreased by 1.8 times (p<0.05), and as a result, the levels became similar in all animals. The levels of sVEGF-R2 in males decreased by 2 times, and in females it increased by 1.4 times (p<0.05), so the sVEGF-R2 content in females became 2.4 times higher than in males. In two-thirds of rats, Stellanin prevented s45 development in the lungs due to inhibition of VEGF-A growth by more than 2.0 times and an increase in concentrations of sVEGF-R1 by 10.0 times and TGF-β by 6.0 times, together with normalization of sVEGF-R2 and sTGFβR2.Conclusions. Stellanin prevents the development of malignant process in the lungs by inhibiting neoangiogenesis (deficiency of VEGF-A and excess of sVEGF-R1) and suppressing the proliferation of malignant cells (TGF-β growth).